Niewydolność serca i płuc, transplantologiaBody wasting in patients referred for heart or lung transplantation. Can we prevent cachexia or avoid serious complications? - Rozentryt, Piotr; Nowak, Jolanta; Sikora, Jacek; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
A large number of epidemiological and observational studies document that unintentional decrease of body weight is associated with higher risk. Chronic diseases and medical procedures resulting in catabolic/anabolic imbalance lead to worse prognosis in persons with low and normal body weight as compared to overweight and slightly obese subjects. A number of diseases, particularly chronic heart failure and chronic obturative pulmonary disease, are well known catabolism inducers and may lead to body wasting. Body wasting is a consequence of long-lasting catabolism/anabolism imbalance. Unlike in simple starvation, body wasting is typically associated with a reduction in either fat or lean body mass. The natural history of chronic diseases comprises periods of relative predominance of anabolism, which may lead to accumulation of fat tissue and increase of body weight. So, in many instances normal body weight coexists with low muscle mass and muscular wasting. The review summarizes strategies focused on prevention of body wasting in heart failure patients and points out potential methods to treat this deadly condition.